Aid in Modulating the Impact of Terrorism on FDI: No Positive Thresholds, No Policy. Issue 4 (2nd October 2021) - Asongu, Simplice A.; Efobi, Uchenna R.; Beecroft, Ibukun
Abstract: We investigate how foreign aid dampens the effects of terrorism on FDI using interactive quantile regressions. The empirical evidence is based on 78 developing countries for the period 1984–2008. Bilateral and multilateral aid variables are used, while terrorism dynamics entail: domestic, unclear, transnational and total number of terrorist attacks. The main finding is that foreign aid cannot be used as a policy tool to effectively address a hypothetically negative effect of terrorism on FDI. The positive threshold we cannot establish is important for policy makers because it communicates a cut-off point at which foreign aid completely neutralizes the negative effect of terrorism on FDI. From the conditioning information set, we also establish for the most part that the effects of GDP growth, infrastructural development and trade openness are an increasing function of FDI. Policy implications are discussed.